2-Hydroxy-4-(Methylthio)-Mutanoate Supplementation Affects Production, Milk Fatty Acid Profile, and Blood Metabolites of High-Producing Holstein Cows - Lourenço, Jean C. S.; Carrari, Isabela F.; Aguiar, Georgia C. de; Janssen, Huibert P.; Lanna, Dante P. D.; Teixeira, Izabelle A. M. A. [UNESP]; Almeida, Rodrigo de (MDPI, 2024)
The objectives of this study were to evaluate the effects of supplementing the diet of high-producing Holstein cows with 2-hydroxy-4-(methylthio)-butanoate (HMTBa) on their milk production and composition, milk fatty acid profile, blood metabolites, and body parameters. The study was conducted in a commercial dairy herd in Paraná State, Southern Brazil. One hundred and fifty-eight multiparous cows were used in a randomized block design during 42 experimental days. Cows were distributed into two treatments: the control treatment cows received 100 g/cow/day of corn meal, while the HMTBa-supplemented cows received 35 g of HMTBa + 65 g/cow/day of corn meal. HMTBa supplementation did not alter milk production but improved milk fat content. Cows receiving HMTBa supplementation showed an increase in the concentration of milk medium-chain fatty acids. Serum levels of blood urea and aspartate aminotransferase were lower in HMTBa-supplemented cows. Cows supplemented with HMTBa increased their body condition score. In summary, HMTB supplementation in high-producing Holstein cows improved productive performance, particularly increased milk fat content, altered milk fatty acid profile, and changed some blood metabolites. Our findings contribute to our understanding of using a methionine analogue as a dietary strategy for optimizing milk quality in high-producing Holstein cows.
Keywords: amino acids; fatty acids; metabolizable protein; methionine analog